Conditions of military contestation in populist Latin America. Issue 5 (29th July 2017) - Kuehn, David; Trinkunas, Harold
ABSTRACT: Latin America experienced recurring episodes of populism, and of military reaction against populists, during the twentieth century, frequently ending in coups d'état. In the twenty-first century, military coups appear to have died out even as populist regimes returned during the third wave of democracy. This paper examines military contestation in populist regimes, both left and right, and how it has changed in the contemporary period. Combining fuzzy set Qualitative Comparative Analysis of Latin American presidencies (1982–2012) and four focused case analyses, we find that military contestation in contemporary populist regimes is driven by radical presidential policies that threaten or actually violate the institutional interests of key elites, among them the military, which in turn is facilitated by the interplay of political, social, economic, and international conditions. Counterintuitively, two of these conditions, the presence of rents and regime capacity for mass mobilization, operate in theoretically unexpected ways, contributing to military contestation.